Penerapan Edukasi Metode Audiovisual terhadap Pengetahuan tentang Anemia pada Ibu Hamil (Journal of Telenursing (JOTING), 2024)
This study aims to determine the application of audiovisual education methods to improve knowledge of anemia in pregnant women. The method in this study used a pre-experiment design with a one-group pretest-posttest design with a sample size of 34 pregnant women. The results obtained using the t-dependent test showed a p-value of 0.000